Loss of regional accent after damage to the speech production network - Berthier, Marcelo L.; Dávila, Guadalupe; Moreno-Torres, Ignacio; Beltrán-Corbellini, Álvaro; Santana-Moreno, Daniel; Torres-Prioris, María José; Massone, María Ignacia; Cruces, Rafael R.; Roé Vellvé, Núria; Thurnhofer-Hemsi, Karl (Frontiers in Human Neuroscience, 2015)
Lesion-symptom mapping studies reveal that selective damage to one or more components of the speech production network can be associated with foreign accent syndrome, changes in regional accent (e.g., from Parisian accent to Alsatian accent), stronger regional accent, or re-emergence of a previously learned and dormant regional accent. Here, we report loss of regional accent after rapidly regressive Broca’s aphasia in three Argentinean patients who had suffered unilateral or bilateral focal lesions in components of the speech production network. All patients were monolingual speakers with three different native Spanish accents (Cordobés or central, Guaranítico or northeast, and Bonaerense). Samples of speech production from the patient with native Córdoba’s accent were compared with previous recordings of his voice, whereas data from the patient with native Guaranítico´s accent were compared with speech samples from one healthy control matched for age, gender, and native accent. Speech samples from the patient with native Buenos Aires’s accent were compared with data obtained from four healthy control subjects with the same accent. Analysis of speech production revealed discrete slowing in speech rate, inappropriate long pauses, and monotonous intonation. Phonemic production remained similar to those of healthy Spanish speakers, but phonetic variants peculiar to each accent (e.g.,